Dynamic response of combined activated sludge-powdered activated carbon batch systems - Ferro Orozco, Ana Micaela (2010)
The objective of this study was to evaluate the effect of powdered activated carbon (PAC) on the growth kinetics of activated sludge; in addition, a kinetic model for this system was developed. Adsorption kinetic experiments of the growth substrate (cheese whey) in the absence of activated sludge were carried out in conical flasks (20 °C, pH 7). Substrate adsorption attained the equilibrium within the first hour. The Langmuir adsorption equation adequately fitted the specific adsorption capacity (qC) as a function of the soluble COD (CODS). Activated sludge batch growth experiments in the presence of different PAC concentrations were also performed. Specific growth rate (μobs) and specific oxygen uptake rate (qO2) decreased as PAC concentration increased; however, stoichiometric coefficients YX/S and YO/S were almost constant. A mathematical model was developed to represent the effect of PAC on the microbial growth kinetics. The model combined biochemical processes (biomass growth, substrate consumption and product generation) with the adsorption kinetics of the substrate onto PAC. A good agreement between the proposed model and the experimental data was obtained. Simulations show that PAC acts as a buffer of substrate, yielding slower responses to changes of the substrate concentration.